Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1539/joh.46.181
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Aromatic Hydrocarbons at a Coke Plant: Part II. Exposure Assessment of Volatile Organic Compounds

Abstract: Occupational Exposure to Aromatic Hydrocarbons at a Coke Plant: Part II. Exposure Assessment of Volatile Organic Compounds: Grażyna Bieniek, et al. Department of Molecular Biology, Biochemistry and Biopharmacy, Faculty of Pharmacy Medical University of Silesia, Poland— The objective of the study is to assess the external and internal exposures to aromatic hydrocarbons in the tar and oil naphthalene distillation processes at a coke plant. 69 workers engaged as operators in tar and oil naphthalene distillation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…It is used in the production of paints, paint thinners, fingernail polish, lacquers, adhesives, and rubber and in some printing and leather tanning processes [11]. Some methods for detection of toluene have been reported such as the detection tube method [12], gas chromatography [13], and chemoresponsive volatile organic compound sensors [14]. The 0.07 ppm toluene value (WHO) emphasizes the need for sensitive, specific, affordable, simple, and reproducible methods for detecting toluene gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used in the production of paints, paint thinners, fingernail polish, lacquers, adhesives, and rubber and in some printing and leather tanning processes [11]. Some methods for detection of toluene have been reported such as the detection tube method [12], gas chromatography [13], and chemoresponsive volatile organic compound sensors [14]. The 0.07 ppm toluene value (WHO) emphasizes the need for sensitive, specific, affordable, simple, and reproducible methods for detecting toluene gas.…”
Section: Introductionmentioning
confidence: 99%
“…Although the detection tube method [12] enjoys simplicity, affordability, and quickness, it is not always easy to read the value off the scale and it relies heavily on the analyst's judgment (subjective). The gas chromatography method [13] is sensitive, specific but its size and its design is not suited as a tool for field operations. Further, it is relatively more costly.…”
Section: Introductionmentioning
confidence: 99%
“…The time weighted average concentrations of aromatic hydrocarbons in the breathing zone air showed that the exposure level of the coke plant workers was rather low 15) , but the GC/MS analysis of the compounds adsorbed from air on active carbon revealed the presence of many different compounds not determined earlier in literature, e.g. : 1,1,3-trimethylcyclohexane, benzofuran, dibenzofuran and biphenyl.…”
Section: Discussionmentioning
confidence: 71%
“…(1) However, long-term exposure to toluene causes dysfunction of the central nervous system, such as constriction of the visual field, ataxia, and amnesia, since it inhibits the enzyme activity of acetylcholinesterase, which catalyzes the hydrolysis of acetylcholine, one of the neurotransmitters in the central nervous system Thus, the maximum permissible concentration [threshold limit value (TLV)] of toluene is prescribed by the American Conference of Industrial Hygienists (ACGIH) as 50 ppm in air for 8 h. (2) Therefore, a sensitive, simple, and reproducible method of detecting gaseous toluene is required to maintain environmental safety for a working person and his surroundings. Some methods of toluene detection have been reported, such as the use of a detection tube, (3) gas chromatography, (4) and semiconductor sensors. (5) However, each method has its advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Although the detection tube method (3) is simple and quick, it cannot be used for continuous measurement. Gas chromatography (4) is sensitive and specific but it is costly and not designed for field operations. Semiconductor gas sensors are not so selective for their target chemicals in the gas phase.…”
Section: Introductionmentioning
confidence: 99%